Clinical Manifestations and Treatment Response of Steroid in Pediatric Hashimoto Encephalopathy. (July 2014) - Yu, Hee Joon; Lee, Jeehun; Seo, Dae Won; Lee, Munhyang
Hashimoto encephalopathy is a steroid-responsive encephalopathy associated with elevated titers of antithyroid antibodies. Clinical symptoms are characterized by behavioral and cognitive changes, speech disturbance, seizures, myoclonus, psychosis, hallucination, involuntary movements, cerebellar signs, and coma. The standard treatment is the use of corticosteroids along with the treatment of any concurrent dysthyroidism. Other options are immunoglobulins and plasmapheresis. We described symptoms and outcomes on 3 teenage girls with Hashimoto encephalopathy. Presenting symptoms were seizure or altered mental status. One patient took levothyroxine due to hypothyroidism before presentation of Hashimoto encephalopathy. After confirmation of elevated antithyroid antibodies, all patients were treated with steroids. One patient needed plasmapheresis because of the lack of response to steroids and immunoglobulins. Hashimoto encephalopathy should be considered in any patient presenting with acute or subacute unexplained encephalopathy and seizures. Even though the use of steroids is the first line of treatment, plasmapheresis can rescue steroid-resistant patients.